Green creativity as a mediator between green human resource management practices and sustainable development: insight from Saudi Arabia - Asma Alfadel; Nisar Nalband (Discover Sustainability)
Abstract Green Human Resource Management (GHRM) has emerged as a key strategic approach for aligning organizational practices with environmental sustainability goals. While prior studies have primarily examined the direct influence of GHRM on sustainable development (SD), limited attention has been given to the mediating role of green creativity (GC), particularly in emerging economies like Saudi Arabia. This study aims to investigate the relationship between GHRM practices and SD, focusing on the mediating effect of GC. Data were collected from 250 employees in diverse private-sector organizations and analyzed using Structural Equation Modeling via Mplus. The findings reveal that GHRM practices positively influence both GC and SD. More importantly, GC significantly mediates the relationship between GHRM and SD. This study highlights the critical role of fostering employee creativity through GHRM practices, such as training, performance management, and employee involvement, to achieve sustainability outcomes. Theoretically, the study extends the application of the theory of planned behavior by positioning GC as a key behavioral mechanism linking HR practices to sustainability outcomes. It also offers practical insights for organizations seeking to enhance their sustainability performance by integrating environmentally focused HRM strategies and cultivating a culture of innovation, in line with the sustainability objectives outlined in Vision 2030. Clinical trial number: “Not applicable.”